2015
DOI: 10.1002/lsm.22331
|View full text |Cite
|
Sign up to set email alerts
|

Laser radiation effect on chondrocytes and intercellular matrix of costal and articular cartilage impregnated with magnetite nanoparticles

Abstract: It was shown that SSNPs do not appreciably affect the structural components of both articular and costal cartilage and can be safely used for the laser diagnostics and therapy. The area of structural alterations is diffuse and local as the result of the mechanical and heat effect of laser impact. SSNPs reveal the areas of the structural alterations of cartilage matrix and give information about the size of the pores and defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…If cartilage tissue has small defects or undergoes laser irradiation with specific pulse‐periodic regime the distribution of pores can be locally significantly extended and the tissue becomes available for the impregnation of larger particles up to 300 nm . The safety of the used NPs for cartilage cells and matrix was shown in . The morphology and crystalline structure of the obtained NPs as well as their thermal and storage stability were analyzed in .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If cartilage tissue has small defects or undergoes laser irradiation with specific pulse‐periodic regime the distribution of pores can be locally significantly extended and the tissue becomes available for the impregnation of larger particles up to 300 nm . The safety of the used NPs for cartilage cells and matrix was shown in . The morphology and crystalline structure of the obtained NPs as well as their thermal and storage stability were analyzed in .…”
Section: Resultsmentioning
confidence: 99%
“…To increase the absorption of the superficial layers of cartilage, we proposed to use clinically approved absorbing magnetite nanoparticles (NPs) modified with biopolymer that enhances their biocompatibility and stability . Impregnation of NPs in avascular cartilage is possible due to the existence of submicron pores in its structure . It was shown that the time of NPs impregnation and extraction can be accelerated by application of magnetic field .…”
Section: Introductionmentioning
confidence: 99%
“…The proteoglycan structure has an electrical nature and positive structure provided by positive ions dissolved in tissue water [ 19 ]. The electrical repulsion of the negatively charged groups is an origin of the stress bringing cartilage sample to its initial shape [ 20 , 21 ]. Therefore, calcified cartilage had poor deformation under the same stress, compared with non-calcified costal cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…The principle working parameter for effective stress relaxation is sufficient temperature. The laser power used in present work was optimized as a result of our previous investigations on ex vivo and in vivo tissue for short‐term generation of the needed temperature field avoiding substantial cell death and collagen denaturation [3,5–7,9,28]. As it is shown here the average laser‐induced temperature for aged human cartilage is even lower than for the healthy one and needs increasing factor to match the optimized temperature.…”
Section: Discussionmentioning
confidence: 99%